ФЕРУЗНИНГ ҲАМД ВА НАЪТЛАРИ - Махаммадиева, Ю. (SCIENCE and SOCIETY, 2020)
There are researched the hamds and nats of Muhammad Rahimhon Feruz - the representative of the Uzbek literature of the national enlightenment. The issue of literary interpretation of the religious-educational theme in his creation been studied on the basis of the analysis of the poet’s masnavies. The secrets of his literary art and poetic mastery are highlighted as well.
Keywords: poetry; hamd; nat; religious-educational theme; literary art; literary skill